Ilhaq al-Masa'il bi Nazairiha dan Penerapannya dalam Bahth al-Masa'il - Luthfi Hadi Aminuddin (AL-TAHRIR, 2013)
Abstract: Ilh}a>q al-Masa>’il bi Naz}a>iriha is one of the methods used by Nahdlatul Ulama in resisting the opinion based on (manhaji) analytical concept of Islamic jurisprudence (the solution for complex social problems as the main purpose of Islamic shari’ah). As known that, up to now, ilh}a>q has been understood as a process of answering a new case by the way of equating to the old one which is written in the book called al-mu’tabarah. Such ilh}a>q has got many criticisms both from the definitions, procedures and its epistemogical footing. This paper is about to reveal how the NU clerics of Islam understand the concept of Ilh}a>q}, what its epistemological footing was and how the concept was applied in discussing many cases (bah}th al-masa>’il). Based on the writer’s study to several documents of decision results of NU that Ilh}a>q did not only simplify to equate the new cases with the old ones that have been freely discussed in the books of al-mu’tabarah, but both cases should have similar legal substance, that is, both should be under the decrees of laws of al-qawa> ‘id al-fiqhi>yah. Thus, Ilh}a>q is actually answering the problem by applying al-qawa>‘id al-fiqhi>yah, whereas the formulation al-qawa>‘id al-fiqhi>yah itself was set off from the examination of a number of furu>’ generated by qiya> s. This paper also found three variations of the implementation of Ilh}a>q in bah}th al-masa>’il. First, the application of Ilh}a>q was without mentioning al-qawa> ‘id al-fiqhi>yah which covered new cases (mulh}aq) and the old case law that has been known in the books of fiqh (mulh}aq bih/attached to). Second, the application of Ilh}a>q was accompanied by mentioning mulh}aq bih and al-qawa> ‘id al-fiqhi>yah. Third, the application of Ilh}a>q, was only by the mentioning al-qawa> ‘id al-fiqhi>yah.